PENERAPAN FUNGSI MANAJEMEN DALAM PENGELOLAAN PERPUSTAKAAN DI SEKOLAH SMP NEGERI 5 MEDAN TAHUN AJARAN 2020/2021 - Syahbilal Syahbilal (Universitas Negeri Medan, 2022)
Application of Management Functions in Library Management at Medan 5 Public Middle School for the 2020/2021 Academic Year. The purpose of this research is to find out what the school currently needs to carry out management functions at SMP Negeri 5 Medan and how the school's future efforts will limit librarian human resources. The method used in this study is qualitative, the source of research data is primary data secondary data, data collection techniques are observation, interviews and documentation. The data collected through this technique is examined and data reduction, data presentation, verification and conclusion are carried out. Based on the results of the study, it was concluded that the first process of implementing management functions in the school library at SMP Negeri 5 Medan could very well be improved in the future. Because all groups in school institutions, stakeholders and layers of the surrounding community have tried to be active and synergize in increasing interest in children's learning services, especially at SMP Negeri 5 Medan, Medan Labuhan District, Martubung Village, Medan City. Second, the role of the government among schools, all processes supporting learning activities in schools such as the facilities and infrastructure at SMP Negeri 5 Medan and other school levels, as well as the central government's active role and motto which wants to educate the life of the nation, this role is also synergized by local government, especially at SMP N 5 Medan, Medan Labuhan District. Third, SMP Negeri 5 Medan, in the future this school will enlarge the library space in the school and increase the number of librarians in the school, by providing special training beforehand so that the function and role of service management in managing the school library can run according to the function of management itself in accordance with the reality of the facts on the ground.